Implementasi Model Pembelajaran Model Mind Mapping Dalam Mengembangkan Karakter Disiplin Siswa Di MAS Miftahussalam Medan - Muhammad Hasan Arifin; Fuji Rahmadi (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This study aims to determine how to implement mind mapping in learning activities and to determine the effect of mind mapping implementation in learning activities on students' character education. Mind mapping is a learning method that uses images, lines, colors, symbols, and simple words to maximize the use of the right and left brain. Mind mapping can help students understand concepts or materials thoroughly, improve memory, and make it easier to organize various information. This study uses a qualitative method with data collection techniques in the form of interviews and observations. This study is expected to examine the implementation of mind mapping in learning activities and its effect on character education